Knyga kaip muziejinis eksponatas Kazio Varnelio bibliotekoje - Braziūnienė, Alma (Knygotyra, 2003)
Kazys Varnelis (b. 1917), a well-known Lithuanian painter, collector and bibliophile, has been collecting rare and antique books as well as maps and museum pieces for most of his life. The collection started while Varnelis was a student at Kaunas Art Institute and Vienna Academy of Fine Arts (1943–1945). His bibliophilic activities became more intensive when Varnelis moved to Chicago in 1949 and also while residing (since 1978) in Stockbridge, Mass. The majority of the books were bought in various European antique shops and auctions (e.g., in Frankfurt, Stockholm, London). Since 1998 the library and museum are located in Prof. Varnelis’ home in Vilnius. The museum of Kazys Varnelis contains collections of paintings, etchings, pieces of sculpture, furniture, ceramics, other arts and crafts, orientalia. 800 museum pieces and 140 personal paintings take up the 36 halls of the museum. The private library of Kazys Varnelis (about 7000 items) holds collections of early Lithuanian books and Lithuanica (15th–early 20th c., 255 items), bibliophilic books (about 1500 items), art history editions, book history and culture editions, fiction, reference books and periodicals, archives. The library also contains a valuable set of old Lithuanian maps (about 170 items). It is an outstanding example of a bibliophilic library. According to Varnelis, a book itself qualifies as a piece of art. On the occasion of the International Conference of Book Science "Bibliophile" (September 20–22, 2001), the main hall of Varnelis’ personal library hosted the exposition of 71 bibliophilic books. Currently, 15 bibliophilic books are exhibited in the same location. Among them – representative pieces of the art of binding, as well as elite edition books from Western Europe and USA (18th–early 20th c.). The elite edition books are distinguished by their luxurious materials, illustrations by famous artists, some states of the same engraving, authentic hand-coloured illustrations etc. In the context of Varnelis’ personal museum, the book as a museum exhibit represents the following functions:• Historical and educational (books are exhibited for the patrons during excursions or official receptions among other museum pieces);• Authentic (the book is an exhibit that preserves historical authenticity);• Visual and aesthetic (books, in particular, bibliophilic books, are exhibited as embodiements of the art of the book because of their artistic bindings and quality). The above statements are best corroborated by the books from Varnelis’ bibliophilic and Lithuanica collections. The museum and the library are presented as Varnelis’ personal interpretation and realization of public cultural heritage.